Compression And Transmission Of JPEG2000 Medical Images Over OFDM For Telemedicine Application - muhamad@Hasnan, Rohaiza (2007)
This study begins with an investigation of lossless and lossy image compression using Kakadu. Kakadu is one of JPEG2000 codec comprises complete implementation of the JPEG2000 standard.